2007
DOI: 10.1063/1.2409612
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and characterization of InAs∕GaAs quantum dot lasers grown using metal organic chemical vapor deposition

Abstract: Ground state lasing at 1.34 μ m from In As ∕ Ga As quantum dots grown by antimony-mediated metal organic chemical vapor deposition Appl. Phys. Lett. 90, 241110 (2007); 10.1063/1.2748082Ground-state lasing of stacked In As ∕ Ga As quantum dots with GaP strain-compensation layers grown by metal organic chemical vapor deposition Quantum dot lasers based on a stacked and strain-compensated active region grown by metal-organic chemical vapor depositionWe report on the lasing characteristics of three-and five-stack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…12. This is attributed to a reduced injection efficiency of carriers into the active region due to increased carrier recombination in the cladding layer [51].…”
Section: B Inas Qd Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…12. This is attributed to a reduced injection efficiency of carriers into the active region due to increased carrier recombination in the cladding layer [51].…”
Section: B Inas Qd Lasersmentioning
confidence: 99%
“…In our QDIP structures, the QDs are undoped and the carriers are supplied through background doping and electron injection from the contact layers. At small electric fields, as the electric field is increased, more electrons populate the QDs, resulting in an increase in the average sheet electron density and hence an increased dark current [51]. When a large fraction of the QD states are filled, further increase of the electric field does not significantly change the sheet electron density.…”
Section: Qd Infrared Photodetectorsmentioning
confidence: 99%
“…Therefore, there won't be any interference between the measured frequency responses because the noise floor is at least 8-10 dBm lower than the measured data point at the lowest current and the frequency of interest increasing the accuracy of extracted lifetime. For both, low and high bias currents we measured the single pole modulation response of 1.1 µm InAs/GaAs quantum dot laser grown using metal organic chemical vapor deposition [11] across the frequency range of interest using the high bandwidth voltage to current convertor circuit as shown in the Fig. 5.…”
Section: Active Circuitmentioning
confidence: 99%
“…Consequently the excited and wetting layer states, which are capable of providing greater gain [24,25], are populated resulting in shorter output wavelengths and increased threshold currents. Work has also indicated that population of the excited and wetting layer states can lead to increased non-radiative recombination [26].…”
Section: Qd Lasersmentioning
confidence: 99%